Effect of feeding different level of Leucaena leucocephala (ipil ipil) leaf meal for rabbit diet (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
This study was conducted to find out the effect of feeding Leucaena leucocephala leaf meal on growth performance and digestibility of nutrients in growing rabbit and to know the cost of rabbit production. For this purpose, a total of twelve unsexed New Zealand White rabbits at 42 days of age were distributed randomly in three treatment groups, i.e. control (T0), adding 10% Leucaena leucocephala leaf meal (T1) in concentrate diet and adding 15% Leucaena leucocephala  leaf meal (T2) in concentrate diet. All diets were iso-energic and iso-nitrogenous. Various aspects of the study, measurements taken in a 56 days experimental period were final body weight gain, feed intake, feed conversion ratio and feeding cost of rabbit production. Results show that the final body weight of rabbits was 1200±30, 1325±85 and 1114±136g, for the treatments of T0, T1 and T2, respectively. The body weights of rabbits were significantly higher in T1 over T2 and T0 groups. The average daily feed intake and feed conversion ratio were 109, 75.55, 83.57g and 9.55, 5.48 and 8.51 for the respective diets/treatments. The growth rate of T0, T1 and T2 treatment groups were 1.05, 1.44 and 0.99, respectively. There was significant effect of different treatment groups on growth rate, feed intake and feed conversion ratio (FCR). The digestibility of dry matter (DM) was the highest in diet T0 followed by diet T2 and T1, respectively. The digestibility of CP was slightly higher for treatment T2 containing 15% Leucaena dry leaf than that of treatment T0 and T1. The digestibility of crude fiber (CF) and ether extract was significantly (P